2009
DOI: 10.5713/ajas.2009.80481
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Full-fat Sunflower Seed for Broiler Chickens

Abstract: Two experiments were conducted to evaluate the use of various levels of full-fat sunflower seeds (FFSS) on broiler performance and carcass characteristics. In the first experiment, FFSS was included in a basal diet at 70, 140, and 210 g/kg and the AME n values of the experimental diets were determined. The linear regression equation of AME n values on rate of inclusion was calculated. Extrapolation value for the AME n of FFSS at 100% inclusion was 14.22 MJ/kg. In the second experiment, diets containing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…On the contrary, the addition of 250 g of HOASS/kg in the diets caused a negative effect on digestive organ sizes. Salari et al (2009) found that the percentages weight of gizzard, breast, thigh, gastrointestinal tract and abdominal fat were not affected by dietary treatments which contained different levels of full fat sunflower seed; while, liver weight % was decreased significantly (P<0.05). Araújo et al, (2011) pointed out that use of sunflower meal up to 15% in the broiler diets did not influence growth performance and carcass and yields during period 22 to 42 days of age.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 79%
See 1 more Smart Citation
“…On the contrary, the addition of 250 g of HOASS/kg in the diets caused a negative effect on digestive organ sizes. Salari et al (2009) found that the percentages weight of gizzard, breast, thigh, gastrointestinal tract and abdominal fat were not affected by dietary treatments which contained different levels of full fat sunflower seed; while, liver weight % was decreased significantly (P<0.05). Araújo et al, (2011) pointed out that use of sunflower meal up to 15% in the broiler diets did not influence growth performance and carcass and yields during period 22 to 42 days of age.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 79%
“…On the contrary, the addition of 250 g of HOASS/kg in the diets caused a negative effect on broiler performance. Feed intake and feed conversion ratio were significantly improved when broiler chickens were fed different inclusions of full fat sunflower seed in the starter (1-3 wk of age) and finisher (3-7 wk of age) diets (Salari et al, 2009). …”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Contrarily, Salari et al (18) pointed out that feed consumption and feed efficiency improved when broilers were given sunflower seed inclusion in the starter and finisher diets.…”
Section: Feed Intake and Feed Conversion Results Inmentioning
confidence: 99%
“…These data are on contrast to (Ologhobo, 1991) who observed that substituting SFM for SBM at levels 50, 75, and 100% decreased the percentages of carcass, dressing and total edible meat. Also, (Salari et al, 2009) found that the percentages weight of gizzard, breast, thigh, gastrointestinal tract and abdominal fat were not affected by dietary treatments which contained different levels of full fat sunflower seed; while, liver weight % was decreased significantly (P<0.05). In addition, (ElSherif et al, 1995) revealed that partial substitution of soybean meal by 5, 10 or 15% of sunflower meal did not result in significant difference in the abdominal fat or carcass component (liver and gizzard) percentages.…”
Section: Some Carcass Traits Of Broiler Chickenmentioning
confidence: 83%